Peningkatan Kreativitas Guru Dalam Mengajar Melalui Pelatihan Model Assure Dengan Pendekatan Scientific Pada Mgmp Pendidikan Agama Islam Di Sekolah Menengah Atas Kabupaten Indragiri Hulu Tahun 2017 - Abdul Kadir (STAIN Bengkalis, 2018)
Creativity is a new invention, in order to fix the problems that occur in the world of education, involving changes in technology and science that is developed today to achieve the goals. The purpose of this action research is to know the Improvement of Teachers’ Creativity in Teaching through Assure Model with scientific approach of MGMP PAI at Senior High School Indragiri Hulu Regency 2017. There were four stages in conducting the research. They were (1) planning, (2) Acting, (3) Observing, and (4) Reflection. From the results of actions research can improve the teachers’ creativity in teaching to achieve the ideal standard after giving training assure model by using approach of scientific is increasing, from pre-training and after training by the observer through (cycle 1) 72.59% to 77.04%, and the second cycle also increased to; 83.33% - 77.04% = 6.30%, The average of teachers’ creativity ability in teaching PAI amounted to 44.44% rose to 100%.